Interlaboratory trial for the measurement of total cobalt in equine urine and plasma by ICP‐MS. Issue 9 (20th June 2017) - Popot, Marie‐Agnes; Ho, Emmie N.M.; Stojiljkovic, Natali; Bagilet, Florian; Remy, Pierre; Maciejewski, Pascal; Loup, Benoit; Chan, George H.M.; Hargrave, Sabine; Arthur, Rick M.; Russo, Charlie; White, James; et al.
Abstract : Cobalt is an essential mineral micronutrient and is regularly present in equine nutritional and feed supplements. Therefore, cobalt is naturally present at low concentrations in biological samples. The administration of cobalt chloride is considered to be blood doping and is thus prohibited. To control the misuse of cobalt, it was mandatory to establish an international threshold for cobalt in plasma and/or in urine. To achieve this goal, an international collaboration, consisting of an interlaboratory comparison between 5 laboratories for the urine study and 8 laboratories for the plasma study, has been undertaken. Quantification of cobalt in the biological samples was performed by inductively coupled plasma‐mass spectrometry (ICP‐MS). Ring tests were based on the analysis of 5 urine samples supplemented at concentrations ranging from 5 up to 500 ng/mL and 5 plasma samples spiked at concentrations ranging from 0.5 up to 25 ng/mL. The results obtained from the different laboratories were collected, compiled, and compared to assess the reproducibility and robustness of cobalt quantification measurements. The statistical approach for the ring test for total cobalt in urine was based on the determination of percentage deviations from the calculated means, while robust statistics based on the calculated median were applied to the ring test for total cobalt in plasma. The inter‐laboratory comparisons in urine and in plasma were successful so that 97.6% of the urine samples and 97.5% of the plasma samples gave satisfactory results. Threshold values for cobalt in plasma and urine were established from data only obtained by laboratories involved in the ring test. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : In order to control the misuse of cobalt, It was necessary to establish an international threshold for cobalt in plasma and/or in urine. An international collaboration, consisting of an interlaboratory comparison, between 5 laboratories for the urine study and 8 laboratories for plasma study has been successfully undertaken.